Early mercaptoacetyltriglycine(MAG‐3) diuretic renography results after pyeloplasty. (25th May 2016) - Faure, Alice; London, Kevin; Smith, Grahame H.H.
Abstract : Objective: To describe the drainage and functional outcome of paediatric pyeloplasty, 1 week after stent removal 7–9 weeks after pyeloplasty using diuretic renography. Patients and Methods: Between 2009 and 2014, we assessed the functional and drainage outcomes according to mercaptoacetyltriglycine MAG‐3 diuretic renograms from 66 children (69 kidneys) who underwent modified dismembered Anderson–Hynes pyeloplasty for pelvi–ureteric junction (PUJ) obstruction. Stents were left in place for 6–8 weeks and postoperative renal units were evaluated with MAG‐3 renogram 1 week after stent removal. Surgical success was defined by improvement of drainage (half clearance time [T/2] < 20 min), stable or improved function on the postoperative MAG‐3 renogram and by decreased pyelocaliceal dilatation on ultrasonography (US) at 1 year. Results: Of the 69 kidneys with a preoperative median range T/2 of 33.4 (7.6–200) min, 60 (87%) had improved drainage curves, with a median (range) T/2 of 6.9 (1.6–19) min. Thirteen percent (9/69) had persistent impaired drainage, with a median (range) T/2 of 36 (24–108) min. Of these nine children, one girl was found to have a persistent obstructive pattern (T/2 = 30 min) associated with a decreased split renal function (SRF; from 42 to 33%) and persistent hydronephrosis (at 28 mm). Redo pyeloplasty was performed 2 months after the initial procedure (and 18 days after stent removal) and renal function recovered to 47%. The remaining eight patients were free of symptoms; hydronephrosis improved at 1 year (anteroposterior diameter decreased from 28 to 18.5 mm; P = 1.94) and SRF remained stable (44.5 vs 48.5% after repair; P = nonsignificant). In the 29% of kidneys (20/69) that had preoperative impaired SRF, postoperative renal function improved in 75% (from 27.5 to 43%; P < 0.001), remained unchanged in 2% and one kidney (0.2%) deteriorated. The median (range) postoperative follow‐up was 18 (12–90) months. Conclusions: There is no agreement regarding the 'gold standard' investigation to use after pyeloplasty for PUJ obstruction. Improvement in hydronephrosis on US is slow and often takes > 12 months. Based on animal studies, it is possible that missed recurrent obstruction will cause irreversible loss of renal function after 6 weeks; therefore, early postoperative assessment is desirable, but there have been few reports on urinary drainage changes with early diuretic renography after pyeloplasty. Most of the renal units had improved drainage on diuretic renography 7 weeks after pyeloplasty and 1 week after stent removal. An early diuretic renogram is a reliable method of documenting surgical success after pyeloplasty